Caracterización de los materiales de subrasante en zonas no urbanizadas de la ciudad de Loja, aplicadas a obras de infraestructura vial en el polígono denominado “Carigan Sur - Márquez Villa, Génesis Meybilin (2015)
The present research is aimed at the study of subgrade materials undeveloped areas of the city of Loja, in this case the area called South Carigan; in order to know the physical characteristics of the soils; they later apply to road infrastructure. To develop the sampling points were assigned on the topographic map of the city of Loja, the same as were disposed to each 500 m apart. Runs was performed within the study polygon for sampling at depths of 0.50 m, 1.00 m and 1.50 m, later proceed to the classification of soils using the AASHTO method further into the depth of 1.50 m trials were run Modified Proctor and CBR; further classification, CBR and abrasion breeding material was determined. Finally, two zoning maps polygon is generated studied, the first according to the classification of the soil and the second based on the ability of the same support. KEYWORDS: